An Inclusive Method for Connecting System-of-Systems Architectures with Stakeholders - Rosanna Zimdahl; Ludvig Knöös Franzén (Systems)
This study addresses the need for early design processes for diverse stakeholder interests in engineering challenges. It does this by using System-of-Systems frameworks, methods, and tools. The presented method, Inclusive SoS Analysis, helps to acquire an overview of the stakeholders’ interests and their preferred System-of-Systems architecture design in an operational setting, and in what way they have conflicting or synergistic interests. The stakeholders are classified by their relationship to the operational execution and integrated broadly throughout the modeling, simulation, and analysis of the System-of-Systems operation—a novel aspect of this work. The proposed method involves three phases: (1) Use case and stakeholder analysis to identify stakeholder interests and define Key Performance Indicators, (2) Modeling and simulation in an agent-based environment to represent System-of-Systems architectures and operational dynamics, and (3) Results and analysis to generate value functions to evaluate the impact of architectural configurations on stakeholder interests. Simulations explore varying System-of-Systems architectures characterized by the constituent systems that compose them, how their collaborative strategy is configured, and how decision making is controlled, revealing the ways in which these factors influence outcomes of the operation. The method is applied to the case study of a complex wildfire fighting scenario with a broad set of stakeholders and multiple constituent systems.